Effect of planting dates and irrigation regimes on productivity and profitability of chickpea (Cicer arietinum L.) under late sown condition - KUMAR, VINOD; MISHRA, S.K. (Journal of Soil and Water Conservation, 2024)
A field experiment was conducted to study the effect of planting dates and irrigation regimes on growth, yield and economics of chickpea (Cicer arietinum L.) at Jawaharlal Nehru Krishi Vishwa Vidyalaya – Zonal Agricultural Research Station, Powarkheda, Narmadapuram during the rabi season of 2015-16. The field experiment comprised three planting dates and four irrigation levels replicated three times in a strip - plot design. Maximum plant height (46.6 cm), mean number of pods per plant (44.5), seed weight per plant (9.2 g), 100 - seed weight (28.9 g), higher grain yield (2989 kg ha-1), net monetary returns (Rs 65,621 ha-1) and benefit: cost ratio (2.75) were recorded in crop sown on 15th November. Maximum seed yield (2678 kg ha-1) was produced by plots which was irrigated twice (branching and pod formation stages), while minimum grain yield (2411 kg ha-1) was produced by plots irrigated three times (branching, pod formation and grain development stages). The irrigation level (branching, pod formation and grain development) recorded maximum gross return (Rs.99,820 ha-1) and net return (Rs.61,081 ha-1) with benefit: cost ratio (2.58). The maximum benefit: cost ratio (2.60) was recorded in irrigation level (branching and pod formation). The information from this study can be used as an important input to suggest planting dates and water management in chickpea.